Kecerdasan Emosional Korelasinya Dengan Prestasi Belajar Matematika Siswa - Rosmalah, Rosmalah; Firdaus, Firdaus; Fitri, Nurul; Amirullah, Amirullah (Universitas Negeri Makassar, 2023)
This is correlational quantitative research that aims to determine whether or not there is a significant relationship between emotional intelligence 986 and mathematics achievement of fifth grade UPTD SPF SDN 3 Lemba District, Lalabata District, Soppeng Regency. The sampling technique is a saturated sample of 47 students. The data collection technique was carried out using a questionnaire and tests for the mathematics subject in the even semester of the 2022/2023 academic year. Data analysis techniques consist of descriptive and inferential analysis. Based on the descriptive results, it shows that emotional intelligence gets an average of 95.28 in the medium category and mathematics learning achievement gets an average of 32.45 in the medium category. Based on the results of the inferential analysis, it shows that at a significance level of 5%, the value of rcount > rtable (0.372 > 0.2876) so it can be concluded that there is significant relationship between emotional intelligence and mathematics learning achievement for fifth grade students of UPTD SPF SDN 3 in the low category at intervals of 0.20 - 0.399.